Population distribution and breeding practices of livestock in different districts of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2023)
The objectives of this study were to determine the farmers’ socio-economic characteristics, livestock population dynamics, and breeding practices followed by the farmers. Out of 1487 farmers, a major proportion (53.12%) of farmers was middle-aged. Most of the farmers (71.22%) were associated with agricultural activities and had low income per month (52.32%). Livestock keeping patterns of farmers were cattle, goats, buffalo, and combinations of these animals. Female animals were inferred to be more prevalent in different districts (cow 85.08%, doe 81.29%) than males (bull 14.92%, buck 18.71%). In case of cattle and goats, the highest number of farmers maintained a medium size herd, whereas buffalo farmers had a large herd size. In terms of breeding practices, the majority of the farmers (75.55%) performed artificial insemination (AI) in cattle and found it convenient to service their cows. When considering buffalo, and goat, the majority of the farmers (94.12% and 98.50%, respectively) practiced natural services. The findings also demonstrated that the majority of the farmers (73.8% and 82%, respectively) raised crossbreed cattle and buffalo, while just a tiny portion (26.18% and 18%, respectively) raised indigenous breeds. However, this situation was vice versa in case of goat. For choice of the breed according to the farmers, 39.17% of farmers preferred Black Bengal goat, 60.83% preferred cross breed.  This study represents a comprehensive overview of livestock status and existing breeding practices employed by the farmers in different districts of Bangladesh, which may be utilized to implement relevant livestock improvement programs in Bangladesh.Asian Australas. J. Biosci. Biotechnol. 2023, 8(3), 38-48